The Potential of Kelakai Leaf Peat Plants (Stenochlaena Palus-tris Bedd) as Sunscreen Based on Sun Protecting Factor (SPF) Values In Vitro - Adelia, Kadek Ayu Cintya; Kurniati, Ety; Kalalinggi, Septaria Yolan (Faculty of Mathtmatics and Natural Sciences, 2025)
Kelakai (Stenochlaena palustris (Burm F.) Bedd) is a type of fern that grows in peat swamp areas or commonly called wetlands. Kelakai leaves contain secondary metabolites, namely flavonoids, which are effective as antioxidants and counteract free radicals. The purpose of this study was to determine whether the extract of kelakai leaves (Stenochlaena palustris (Burm.F.) Bedd) has sunscreen protection activity.UV radiation or known as ultraviolet consists of 2 types, namely: UV-A and UV-B, the letter A in UV-A means